SAE Technical Paper Series 2005
DOI: 10.4271/2005-01-3327
|View full text |Cite
|
Sign up to set email alerts
|

Strategies for Burr Minimization and Cleanability in Aerospace and Automotive Manufacturing

Abstract: The quality of machined components in the aerospace and automotive industries has become increasingly critical in the past years because of greater complexity of the workpieces, miniaturization, usage of new composite materials, and tighter tolerances. This trend has put continual pressure not only on improvements in machining operations, but also on the optimization of the cleanability of parts. The paper reviews recent work done in these areas at the University of California-Berkeley. This includes: Finite e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 7 publications
0
8
0
Order By: Relevance
“…Cleanability and burr reduction which are another green manufacturing aspects also on the machine level were studied in various machine tool researches to act as another optimization objectives in their attempts to improve machine tool performance. Example of this type of work was presented by Avila et al (2005) in the aerospace industry.…”
Section: Reducementioning
confidence: 97%
“…Cleanability and burr reduction which are another green manufacturing aspects also on the machine level were studied in various machine tool researches to act as another optimization objectives in their attempts to improve machine tool performance. Example of this type of work was presented by Avila et al (2005) in the aerospace industry.…”
Section: Reducementioning
confidence: 97%
“…In one work, process control chart was made 15 for predicting burr formation and tool life, and to minimize burr size. Avila et al reported 16 a detailed recommendation on minimization of burrs in aerospace and automotive component manufacturing, whereas Chern 17 investigated on burr formation mechanisms in face milling process, and influence of cutting conditions on burr formation in three different aluminum alloys. Burr geometry was found to be strongly dependent upon in-plane exit angle.…”
Section: Introductionmentioning
confidence: 99%
“…[8][9][10] By collecting the existing information about the relationship between the process parameters and burr type, drilling burr control chart, which is material specific, is utilized to decide the optimized cutting speed and feed rate for burr minimization. 4,11 These approaches have laid solid foundation for burr control. However, the interlayer gap contributes more to the interfacial burr formation than other factors, and these results make less difference to minimize the interfacial burr than expected.…”
Section: Introductionmentioning
confidence: 99%